Science Scientific Knowledge and COVID 19 in the Chair of Scientific Research Methodology - Vivian Aurelia Minnaard (Newinera Publisher, 2021)
The objective of this work was: To investigate the degree of participation of medical students from a privately managed university in the city of Mar del Plata, Argentina, in the recovery activity in October 2021 and the associations they make between the topics presented.The research was developed in a descriptive way with a non-experimental design. The practical work was proposed for the students to do it asynchronously within a week, with daily monitoring by the teaching team. The sample selected in a non-probabilistic way for convenience is 16 fourth-year students studying MethodologyThe most frequent characteristics of the scientific knowledge identified by the students were descriptive, explanatory and predictive It is striking that none recognized the provisional nature of the knowledge that flowed permanently with the information provided by the sources consulted.It is interesting to note that the number of views was 200, therefore if an average per student of 12.5 views of this resource available on the web offers the possibility of a truly enriching exchange. As heads of chairs such as Methodology where students begin to go through the steps of an investigation,it is necessary to look for alternatives within the available resources that motivate students, generating curiosity, synergy and proactivity. Promoting spaces for the exchange of opinions, information transfer is key to strengthen skills associated with critical thinking and communication. New technologies by providing the possibility of asynchrony and synchrony allow a fluidity in the exchanges between the teaching body and the students.